The impact of accounting information systems on the profession of external auditing - Field study of a sample of external auditors in Algeria- - necira, bilal; Bouzidi, abderrouf (Journal of Research in Finance and Accounting, 2020)
This is study aims to know the impact accounting information systems on the profession of external auditing, Through academics and professionals in Algeria, we have prepared a questionnaire on account governors and Experts and academics. This study found that accounting information systems effect on the profession of external auditing directly.